Estimation of the Lifespan of Agricultural Tractor Using a Diffusion Model at the Aggregate Level [Estimación de la Vida Útil del Tractor Agrícola Mediante el Uso de Un Modelo de Difusión a Nivel Agregado] - Llanos-Ascencio, J (2012)
The adoption of agricultural tractors by farms has resulted in different combinations, relationships and established ways of production of localities, regions and countries. The dynamics of the tractorization process are defined by the balance of the units that enter the fleet and those that are removed at the end of their useful life. This study uses a diffusion pattern and aggregated adoption of the agricultural tractor, the parameters of which were determined using a nonlinear estimation procedure and country-level data for Chile. Using the predictive power of the model, a longitudinal series of tractor fleets was estimated, and then the balance was calculated considering the units that were discharged. To more accurately determine the average lifespan of a tractor, successive iterations were performed to reduce differences with respect to a control variable for the number of tractors registered. The estimated average lifespan for agricultural tractors at the aggregate level is 22 years. This type of estimation procedure can be used not only for descriptive purposes, as in this case, but also for predictive purposes. © 2013 Pontificia Universidad Católica de Chile.